Science and evidence informing policymaking in New Zealand: The meth contamination story - Bardsley, Anne (New Zealand Science Review, 2018)
The following is based on a presentation given at the NZAS 2018 Annual Conference New Zealand Perspectives at the Interface of Science and Policy, and provides a brief overview of the complex story that led to the most dramatically impactful report produced during Sir Peter Gluckman’s tenure as the Prime Minister’s Chief Science Advisor – ‘Methamphetamine contamination in residential properties: Exposures, risk levels, and interpretation of standards’ (Gluckman et al. 2018). Release of the report rapidly shifted policies across a number of government agencies and abruptly curtailed the predatory practices of an industry which had flourished because of a particular failure in the science-to-policy exchange: no one had asked the right question